The impact of the COVID-19 lockdown on depression sufferers: a qualitative study from the province of Zaragoza, Spain - Alejandra Aguilar-Latorre; Bárbara Oliván-Blázquez; Ana Porroche-Escudero; Fátima Méndez-López; Valentín García-Gallego; Belén Benedé-Azagra; Rosa Magallón-Botaya (BMC, 2022)
Abstract Background and purpose The impact of COVID-19 and its control measures have exacerbated existing mental health conditions. Although the deleterious effects of mental health problems are well known, fewer studies have examined the links between the Social Determinants of Health (SDHs) and depression. This study provides insights into the relationship between SDHs and depression during the first strict lockdown in Spain, which lasted for a period of 7 weeks. Methods Fifty-two structured interviews were conducted with people diagnosed with depression during June 2020 in the province of Zaragoza (Spain). Interviews were conducted by telephone due to lockdown constraints. Inductive thematic content analysis was used to explore, develop, and define emergent categories of analysis, which were mapped against the SDH framework. Results Listening to people's experiences of living with depression during lockdown provided insights into their concerns and coping strategies, which are greatly influenced by the conditions in which they live, their job and their age. Examples of these factors include access to and quality of physical spaces, including housing conditions and public spaces for socialising, social support, adverse working conditions which include caring responsibilities, and access to digital technologies and healthcare services. Conclusion SDHs have played a fundamental role in shaping people's health and well-being during the COVID-19 pandemic, and this study has shown that they have a considerable effect on depression outcomes. Governments should consider implementing social welfare programs to tackle both psychosocial problems and material need during crisis situations.